2013
DOI: 10.1371/journal.pone.0067920
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Both n-3 and n-6 Long-Chain Polyunsaturated Fatty Acids in Cord Serum Phospholipids Predict Allergy Development

Abstract: BackgroundLong-chain polyunsaturated fatty acids (LCPUFAs) reduce T-cell activation and dampen inflammation. They might thereby counteract the neonatal immune activation and hamper normal tolerance development to harmless environmental antigens. We investigated whether fatty acid composition of cord serum phospholipids affects allergy development up to age 13 years.MethodsFrom a population-based birth-cohort born in 1996/7 and followed until 13 years of age (n = 794), we selected cases with atopic eczema (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 61 publications
(68 reference statements)
1
31
0
Order By: Relevance
“…Our findings confirm the delivery of maternal dietary changes during pregnancy to the infant, the TAG FA representing a biomarker of exposure to exogenous FA over a very recent period of dietary intake (Lagström et al, 1998). The modification of infant's FA status at an early stage may be of importance and carry long-term health benefits up to adulthood (Barman et al, 2013;Kaikkonen et al, 2012). Dietary counseling, an approach applicable to public health setting, resulted in increased intakes of nÀ3 FA in the intervention group over the entire course of pregnancy and lactation, also reported previously in the larger study population (Ilmonen et al, 2011;Piirainen et al, 2006) Continuous supply of FA from the usual diet was ensured through supporting dietary counseling with provision of rapeseed oil based food products from early pregnancy onwards.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our findings confirm the delivery of maternal dietary changes during pregnancy to the infant, the TAG FA representing a biomarker of exposure to exogenous FA over a very recent period of dietary intake (Lagström et al, 1998). The modification of infant's FA status at an early stage may be of importance and carry long-term health benefits up to adulthood (Barman et al, 2013;Kaikkonen et al, 2012). Dietary counseling, an approach applicable to public health setting, resulted in increased intakes of nÀ3 FA in the intervention group over the entire course of pregnancy and lactation, also reported previously in the larger study population (Ilmonen et al, 2011;Piirainen et al, 2006) Continuous supply of FA from the usual diet was ensured through supporting dietary counseling with provision of rapeseed oil based food products from early pregnancy onwards.…”
Section: Discussionsupporting
confidence: 75%
“…Early modification of infant's FA status by increasing the proportion of unsaturated FA, particularly nÀ3 FA, may be of importance both in the short and long term, benefits possibly extending up to adulthood (Barman et al, 2013;Kaikkonen et al, 2012). However, as no changes in the CE FA or FA at 1 month of age were detected, it may be speculated that more drastic measures, such as supplementation of FA, in either maternal or infant diet may be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found increased maternal fish intake protects against eczema at 1 year of age, and against atopy and atopic wheeze at 6 years, especially among children who were not breastfed . Maternal PUFA supplementation during pregnancy reduces atopic eczema and egg sensitization in the first year of life , yet higher levels of LCPUFAs in cord serum are associated with increased risk of allergy . Another study showed that during the first trimester, maternal shellfish consumption increases the risks of wheezing and eczema, and fatty fish consumption increases the risk of asthma, although lean fish and total fish consumption did not affect allergic disease risk .…”
Section: In Utero Exposures That Influence Allergymentioning
confidence: 99%
“…A meta-analysis concluded that maternal supplementation during pregnancy with n-3 PUFA was associated with decreased childhood asthma, allergic skintest responses to egg, and reduced levels of interleukin (IL)-13 (Klemens et al, 2011). However a recently reported study of neonatal cord blood levels showed that risk of respiratory allergy at age 13 years increased linearly with the proportion of n-3 or n-6 PUFA in cord blood serum and decreased linearly with the proportions of total medium chain PUFA levels, suggesting to the investigators that reduced inflammatory response in this period may prevent activation of immune response, leading to tolerance toward harmless environmental antigens (Barman et al, 2013). PUFAs target T-helper type 1 (Th1) cells activated by microbial exposure, whereas Th2 cells, which support the development of IgEmediated allergy, are not suppressed by either n-3 or n-6 PUFAs to the same extent (Wallace et al, 2001).…”
Section: Long-chain Polyunsaturated Fatty Acidsmentioning
confidence: 99%